1996
DOI: 10.1097/00000433-199603000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Infarction and Intracranial Arterial Dissection in Closed Head Injury

Abstract: This report describes the autopsy findings in three cases of closed head injury dying of cerebral infarction, with brain swelling and herniation. In each instance the cause of the infarct was found to be subintimal dissection involving intracranial anterior circulation arteries. The autopsy findings underscore the value of histological examination of vessels that macroscopically appear thrombosed. We discuss factors that impact on the reported incidence and make brief mention of problems surrounding the true p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Arterial dissections in both the anterior and posterior circulation often have no associated causative factors (spontaneous) or may be associated with minor and major head trauma and a variety of other factors such as connective tissue disease. Adults and children may be affected 8,17,19,21,22,24,25 . The angiographic criteria for diagnosis of dissecting aneurysm have been described 9,13 .…”
Section: Intracranial Dissectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arterial dissections in both the anterior and posterior circulation often have no associated causative factors (spontaneous) or may be associated with minor and major head trauma and a variety of other factors such as connective tissue disease. Adults and children may be affected 8,17,19,21,22,24,25 . The angiographic criteria for diagnosis of dissecting aneurysm have been described 9,13 .…”
Section: Intracranial Dissectionmentioning
confidence: 99%
“…The calcification of the PCA wall on CT implies that this is a chronic lesion associated with her fall ten years ago. It is unclear how indirect or remote trauma can cause dissection 22 . It has been suggested that shearing and rotational injury with significant intensity can disrupt the vessel wall, but not severe enough to cause complete disruption 1 .…”
Section: Intracranial Dissectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arterial dissections in both the anterior and posterior circulation often have no associated causative factors (spontaneous) or may be associated with minor and major head trauma and a variety of other factors such as connective tissue disease. Adults and children may be affected 8,17,19,21,22,24,25 . The angiographic criteria for diagnosis of dissecting aneurysm have been described 9,13 .…”
mentioning
confidence: 99%
“…It has been suggested that shearing and rotational injury with significant intensity can disrupt the vessel wall, but not severe enough to cause complete disruption 1 . Various contributory etiological factors such as polyarteritis nodosa, cystic medial necrosis, atherosclerosis, fibromuscular disease, Marfan's syndrome, mixed connective tissue disease, migraine and electrocution have been reported 9,22 . The close proximity of the posterior cerebral artery to the free edge of the tentorium may not require much force to directly traumatize the artery against the tentorium.…”
mentioning
confidence: 99%